Initial vegetative growth of coffee plants submitted to foliar spraying of Paclobutrazol - d’Arêde, Lucialdo Oliveira; Matsumoto, Sylvana Naomi; Santos, Jerffson Lucas; Viana, Anselmo Eloy Silveira; Ramos, Paula Acássia Silva (Coffee Science - ISSN 1984-3909, 2017)
The objective of this study was evaluate the initial vegetative growth of plants cv. CatuaíVermelho IAC 144 submitted to foliar spraying of four solutions concentrations (250, 500, 750 and 1000 mg L-1) of pacloblutrazol (PBZ) and a control. The plants were cultivated in a greenhouse, in a randomized blocks experimental design, with five treatments and four replicates, evaluated at 120 days after PBZ application. The data were subjected to general and regression analysis of variance. All of morphological characteristics were affected by PBZ, with growth reduction of the coffee crown and lifting the root dry weight in comparison to the control plants. PBZ results in elevation of the SPAD index, xylem water potential, net photosynthesis rate and carboxylation efficiency of coffee plants. Net photosynthesis rate was affected by carboxylation efficiency, and transpiration was associated with greater water availability. The PBZ changes the relationship between the shoot and root growth, increasing the growth of roots and optimizes the relations of leaf gas exchange, due to elevation of plant water status.PBZ effects in morphological characteristics in initial growth of coffee plants are more evident in comparison to physiological alterations.